Endothelial erosion of plaques as a substrate for coronary thrombosis - White, Stephen J.; Newby, Andrew C.; Johnson, Thomas W. (Thrombosis and Haemostasis, 2016)
Myocardial infarction is a prevalent, life-threatening consequence of athero-thrombosis. Post-mortem histology and intravascular imaging in live patients have shown that approximately one third of myocardial infarctions are caused by a thrombus overlying an intact, non-ruptured atherosclerotic plaque. Histology identifies erosion of luminal endothelial cells from smooth muscle and proteoglycan-rich, thick fibrous cap atheromas as the underlying pathology. Unlike plaque ruptures, endothelial erosions tend to occur on thick-capped atherosclerotic plaques and may or may not be associated with inflammation. Smoking and female gender are strong risk factors for erosion. Multiple mechanisms may contribute to endothelial erosion, including endothelial dysfunction, TLR signalling, leukocyte activation and modification of sub-endothelial matrix by endothelial or smooth muscle cells, which may trigger loss of adhesion to the extracellular matrix or endothelial apoptosis. Diagnosis of endothelial erosion by intravascular imaging, especially high resolution optical coherence tomography, may influence treatment strategies, offering prognostic value and utility as an endpoint in trials of agents designed to preserve an intact coronary endothelium.
Keywords: Atherothrombosis; endothelial cells; imaging; shear stress